Moderasi dan Literasi: Militansi Pendidikan Kristen dalam Menghadapi Tantangan Ujaran Kebencian di Era Digital - Zega, Yanuar Ada; Bilo, Dyulius Thomas (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
Moderation and literacy are effective approaches integrated in Christian religious education to counteract conflict in the digital space. Christian religious education has an important role in shaping the character and morals of Christians in a social environment that emphasizes the values of love, tolerance and mutual respect. However, in this connected digital era, new challenges arise in the form of hate speech that can threaten peace and unity. Hate speech on social media also damages the spiritual development of individuals. This research uses a literature data collection method with a descriptive qualitative approach. It found that the principles of moderation teach the importance of avoiding extremism and communicating wisely and are supported by the principles of digital literacy that help learners to critically understand, analyze, and appreciate the information they encounter. Solutive recommendations in the form of moderation and literacy principles in addressing the apparent problems in this topic will be elaborated by quoting Bible verses that emphasize emotion management, time management, and awareness of the impact of extremism.